2023
DOI: 10.2500/aap.2023.44.230035
|View full text |Cite
|
Sign up to set email alerts
|

Proton-pump inhibitors are associated with an increased risk of asthma: A nationwide nested case-control study

Wei-Ting Wang,
Cheng-Yuan Li,
Yun-Ting Chang
et al.

Abstract: Background: Proton-pump inhibitors (PPI) are among the most widely used drugs worldwide. However, the association between PPI use and the risk of asthma remains unclear. Objective: To investigate the association between PPI use and subsequent asthma risk. Methods: We included participants from the Taiwan National Health Insurance Research Database between 1999 and 2013. Patients who used PPIs and experienced new-onset asthma (n = 20,344) were assigned to the case cohort and matched in a 1:1 ratio with contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…In this study, we hypothesized that a low pH might be associated with the development of allergic disease and asthma. On the other hand, there is emerging evidence that regular use of proton-pump inhibitors (PPI) in children resulting in a higher pH in the gastrointestinal tract is in fact associated with an increased risk of asthma [26,27]. Studies also showed association between the use of acid suppressive medications in children and an increased risk of other allergic diseases, such as food allergy, anaphylaxis, and allergic rhinitis [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we hypothesized that a low pH might be associated with the development of allergic disease and asthma. On the other hand, there is emerging evidence that regular use of proton-pump inhibitors (PPI) in children resulting in a higher pH in the gastrointestinal tract is in fact associated with an increased risk of asthma [26,27]. Studies also showed association between the use of acid suppressive medications in children and an increased risk of other allergic diseases, such as food allergy, anaphylaxis, and allergic rhinitis [28,29].…”
Section: Discussionmentioning
confidence: 99%